A new trans-Andean Stick Catfish of the genus Farlowella Eigenmann & Eigenmann, 1889 (Siluriformes: Loricariidae) with the first record of the genus for the río Magdalena Basin in Colombia - Ballen, Gustavo A.; Mojica, José Iván (Zootaxa, 2014)
A new species of Farlowella is described from El Carmen de Chucurí in the Departamento de Santander, western flank of the Cordillera Oriental, río Magdalena Basin, Colombia. Farlowella yarigui n. sp. differs from its congeners in lateral body plate morphology, abdominal cover, cephalic hypertrophied odontodes, and details of coloration. This is the first verifiable record of the genus in the Magdalena drainage. Aspects of natural history and implications of this finding are provided concerning the state of knowledge of the fishes of the río Magdalena Basin. Previous records of Farlowella gracilis in the río Cauca basin are examined and herein considered erroneous, rendering the new species the only representative of the genus in the Magdalena-Cauca system. A key to species of Farlowella from Colombia is provided.